2021
DOI: 10.3390/polym13162780
|View full text |Cite
|
Sign up to set email alerts
|

The Blending of Poly(glycolic acid) with Polycaprolactone and Poly(l-lactide): Promising Combinations

Abstract: Poly(glycolic acid) (PGA) holds unique properties, including high gas barrier properties, high tensile strength, high resistance to common organic solvents, high heat distortion temperature, high stiffness, as well as fast biodegradability and compostability. Nevertheless, this polymer has not been exploited at a large scale due to its relatively high production cost. As such, the combination of PGA with other bioplastics on one hand could reduce the material final cost and on the other disclose new properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…The melting peak is bimodal (209.1 and 218.9 °C) for the second heating–cooling cycle. This is possibly due to the melt-recrystallization phenomena, which is very common in the crystallization of polyesters. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The melting peak is bimodal (209.1 and 218.9 °C) for the second heating–cooling cycle. This is possibly due to the melt-recrystallization phenomena, which is very common in the crystallization of polyesters. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…This is possibly due to the melt-recrystallization phenomena, which is very common in the crystallization of polyesters. 58,59 The livingness of the ROP of GL catalyzed by organobase t BuP 2 and TU4 in diluted FA was demonstrated by the sequential addition of monomers (chain-extension experiment). The reaction time was prolonged to 15 min to ensure quantitative conversion before adding the same equivalent monomer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Based on the enthalpy values, the crystalline phase content (crystallinity, X c ) was calculated according to the following Equation (10): where Δ H m is enthalpy of melting, Δ H c is enthalpy of cold crystallization and Δ H mi,100% is enthalpy of melting for a fully (100%) crystalline homopolymer (literature data). The values of 106 J g −1 [ 21 ], 136 J g −1 [ 22 ] and 191 J g −1 [ 23 ] for Δ H m,100% of PLA, PCL and polyglycolide were used respectively. W i is the weight fraction of the Cap, LL and GG co-units in copolymers; for homopolymers, W i = 1.…”
Section: Methodsmentioning
confidence: 99%
“…We showed that synthetic scaffolds based on linear polyesters retained 30–50% of their initial strength after 3 months of exposure in a model media simulating the environment of bile ducts [ 54 ]. We hypothesized that a multi-layered design would be beneficial for the creation of a bioengineered equivalent of the bile duct based on polymers with various degradation properties (PCL, PLCL, and PLGA) using an electrospinning technique [ 55 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%